Qualitative Study on the Effect of Workload and Motivation on Performance with Supervision and SOP as Mediator Variables - Sahabuddin, S.; Jumady, Edy; Fajriah, Yana (Manunggal Halim Jaya, 2025)
This study explores the complex relationships between workload, motivation, employee performance, and the mediating roles of supervision and standard operating procedures (SOPs) in organizational contexts. Using a qualitative research methodology based on a systematic literature review, the study synthesizes findings from both theoretical and empirical research to understand how these variables interact and influence performance outcomes. Data was collected from peer-reviewed journals, books, and organizational behavior, psychology, and management case studies. The analysis uses thematic coding to identify patterns and themes within the literature, shedding light on how the workload can act as both a motivator and a stressor, depending on the support systems in place. The findings indicate that intrinsic motivation is crucial in driving sustainable performance, while supervision and SOPs are important mediators that help stabilize performance and reduce workload-related stress. Adequate supervision, characterized by supportive guidance and feedback, enhances employee resilience in high demands, while SOPs provide structure and consistency in task execution. These results have significant theoretical implications for frameworks such as the Job Demands-Resources (JD-R) model, self-determination theory, and Leader-Member Exchange (LMX) theory. Additionally, the study offers practical recommendations for management strategies aimed at promoting sustainable employee performance. Ultimately, this research emphasizes the importance of balancing workload, intrinsic motivation, and structured support to cultivate a high-performing and resilient workforce.